2020
DOI: 10.1002/jha2.39
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of children with polycythemia vera, essential thrombocythemia, and primary myelofibrosis in Japan: A retrospective nationwide survey

Abstract: Background Philadelphia‐negative (Ph‐negative) myeloproliferative neoplasms (MPNs), including polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF), are exceptionally rare during childhood. Thus, clinical features of pediatric Ph‐negative MPNs remain largely unknown. This study was therefore performed to address this. Methods We performed a retrospective study to collect clinical information of children diagnosed with Ph‐negative MPNs from 2000 to 2016 using questionnaires in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Although the causes and formation mechanisms of primary thrombocytosis are not fully elucidated, infections were identified as the most common causes of secondary thrombocytosis in many studies. In a study, the most common causes of severe thrombocytosis were infections in 80 (56.8%) patients, anemia in 21 (14.9%) patients, and autoimmune diseases in 14 (9.9%) patients 9 . Clemens Stockklausner et al reported that the most common causes were infections (49.5%), postsplenectomy (7.8%), Kawasaki disease (6.4%), tissue damage (4.5%), blood diseases (3.7%), malignancies (3.7%), renal diseases (3.2%), chronic inflammation (1.8%), essential thrombocythemia (0.5%), and other causes (3.7%) 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the causes and formation mechanisms of primary thrombocytosis are not fully elucidated, infections were identified as the most common causes of secondary thrombocytosis in many studies. In a study, the most common causes of severe thrombocytosis were infections in 80 (56.8%) patients, anemia in 21 (14.9%) patients, and autoimmune diseases in 14 (9.9%) patients 9 . Clemens Stockklausner et al reported that the most common causes were infections (49.5%), postsplenectomy (7.8%), Kawasaki disease (6.4%), tissue damage (4.5%), blood diseases (3.7%), malignancies (3.7%), renal diseases (3.2%), chronic inflammation (1.8%), essential thrombocythemia (0.5%), and other causes (3.7%) 10 .…”
Section: Discussionmentioning
confidence: 99%